2013
DOI: 10.1371/journal.pone.0072686
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Analyses of Muscle Transcriptomes in Dorper and Small-Tailed Han Sheep Using RNA-Seq Technique

Abstract: The sheep is an important domestic animal and model for many types of medically relevant research. An investigation of gene expression in ovine muscle would significantly advance our understanding of muscle growth. RNA-seq is a recently developed analytical approach for transcriptome profiling via high-throughput sequencing. Although RNA-seq has been recently applied to a wide variety of organisms, few RNA-seq studies have been conducted in livestock, particularly in sheep. In this study, two cDNA libraries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 37 publications
5
56
3
Order By: Relevance
“…In the two sheep breeds, we found similar AS rates, with 35.69, 34.03, 34.50, 38.33, 37.46, and 30.54% of the reference genes in the six libraries undergoing 24,239,22,283,22,457,26,635,27,093, and 18,700 AS events. This is much lower than that reported for humans (86.0%) (Wang et al, 2008), but is higher than that reported for pigs (18.0%) (Chen et al, 2011), sheep (25.28-26.02%) (Zhang et al, 2013), and rice (33.0%) (Zhang et al, 2010). The most common AS identified in our research was IR, in both Mongolian and Lanzhou fat-tailed sheep.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the two sheep breeds, we found similar AS rates, with 35.69, 34.03, 34.50, 38.33, 37.46, and 30.54% of the reference genes in the six libraries undergoing 24,239,22,283,22,457,26,635,27,093, and 18,700 AS events. This is much lower than that reported for humans (86.0%) (Wang et al, 2008), but is higher than that reported for pigs (18.0%) (Chen et al, 2011), sheep (25.28-26.02%) (Zhang et al, 2013), and rice (33.0%) (Zhang et al, 2010). The most common AS identified in our research was IR, in both Mongolian and Lanzhou fat-tailed sheep.…”
Section: Discussioncontrasting
confidence: 71%
“…The most common AS identified in our research was IR, in both Mongolian and Lanzhou fat-tailed sheep. Our results were similar to those for rice (Zhang et al, 2010), but different from those for pigs (Chen et al, 2011) and Dorper and small-tailed Han sheep (Zhang et al, 2013), in which A3SS was identified as the most common AS. Our results also differed from those of humans (Sultan et al, 2008), in which ES was the primary type of AS.…”
Section: Discussionsupporting
confidence: 60%
“…The Dorper breed of sheep is a fast-growing meat-producing sheep originated from South Africa, and is renowned for its hardiness, early sexually maturity, lean carcass and high growth rate. The breed has been widely used as a terminal sire breed to improve the growth performance and carcass traits of lambs (Zhang et al 2013;Xing et al 2014). The Jinzhong breed is an indigenous sheep breed that demonstrates strong adaptability to local conditions in Shanxi province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of gene expression profiles in sheep muscles by Lobo et al (2012) revealed differential expression of MyoD1 and IGFBP4 genes associated with breed and productive qualities. In addition, Zhang et al (2013) studied gene expression in two sheep breeds by RNA sequence analysis and revealed significant differences in more than 1,300 genes. Continued research has allowed these researchers to describe 34 genes with differential expression related to the development and differentiation of muscle cells .…”
Section: Introductionmentioning
confidence: 99%